Timeliness and quality of peripartum care provision during a health system strengthening initiative in rural Guinea-Bissau: a qualitative situation analysis - Sabine Margarete Damerow; Helene Vernon Adrian; Bucar Indjai; Elsi José Carlos Cá; Nanna Maaløe; Ane Bærent Fisker; Jane Brandt Sørensen (BMC, 2024)
Abstract Guinea-Bissau has among the world's highest maternal and perinatal mortality rates. To improve access to quality maternal and child health (MCH) services and thereby reduce mortality, a national health system strengthening initiative has been implemented. However, despite improved coverage of MCH services, perinatal mortality remained high. Using a systems-thinking lens, we conducted a situation analysis to explore factors shaping timeliness and quality of facility-based care during labour, childbirth, and the immediate postpartum period in rural Guinea-Bissau. We implemented in-depth interviews with eight peripartum care providers and participant observations at two health facilities (192 h) in 2021-22, and analysed interview transcripts and field notes using thematic network analysis. While providers considered health facilities as the only reasonable place of birth and promoted facility birth uptake, timeliness and quality of care were severely compromised by geographical, material and human-resource constraints. Providers especially experienced a lack of human resources and materials (e.g., essential medicines, consumables, appropriate equipment), and explained material constraints by discontinued donor supplies. In response, providers applied several adaptation strategies including prescribing materials for private purchase, omitting tests, and delegating tasks to birth companions. Consequences included financial barriers to care, compromised patient and occupational safety, delays, and diffusion of health worker responsibilities. Further, providers explained that in response to persisting access barriers, women conditioned care seeking on their perceived risk of developing birthing complications. Our findings highlight the need for continuous monitoring of factors constraining timeliness and quality of essential MCH services during the implementation of health system strengthening initiatives.